Self pumping magnetic cooling. (19th December 2016) - Chaudhary, V; Wang, Z; Ray, A; Sridhar, I; Ramanujan, R V
Abstract: Efficient thermal management and heat recovery devices are of high technological significance for innovative energy conservation solutions. We describe a study of a self-pumping magnetic cooling device, which does not require external energy input, employing Mn–Zn ferrite nanoparticles suspended in water. The device performance depends strongly on magnetic field strength, nanoparticle content in the fluid and heat load temperature. Cooling (Δ T ) by 20 °C and 28 °C was achieved by the application of 0.3 T magnetic field when the initial temperature of the heat load was 64 °C and 87 °C, respectively. These experiments results were in good agreement with simulations performed with COMSOL Multiphysics. Our system is a self-regulating device; as the heat load increases, the magnetization of the ferrofluid decreases; leading to an increase in the fluid velocity and consequently, faster heat transfer from the heat source to the heat sink.